Comparative Analysis of the Most Industrialized Cities in Turkey from the Perspective of Industry 4.0 - Gergin, Zeynep; ILHAN, DOGAN AYBARS; Gençyılmaz, M.Güneş; DÜNDAR, Uğurcan; Çavdarlı, Ali İhsan; YÜKSEKTEPE, FADİME ÜNEY (My University, 2019)
It can be declared that the adaptation of companies to the new industrial revolution, so called Industry 4.0, is not a choice but an issue of survival. The structure of business processes are changing with the newly introduced, radical and highly value adding technological drivers, such as internet of things, cloud computing, autonomous robots, augmented reality, cyber security system, etc. In the globalized trade markets none of the companies can close their eyes to this new era and ignore the required change in their operations. Small and Medium Sized Enterprises (SMEs) have 99.8% enterprise share of Turkey, and consequently have obvious contribution not only to the local economy but also to the global competition strength of the country. In that sense, catching up the fourth industrial revolution has to be the prior agenda of the SMEs, and also of the government institutions and the universities from the perspective of giving the required support. This study is the continuum of the broad research that is initiated in March 2018. The purpose is to identify the current situation of SMEs in Turkey with respect to their various implementations for Industry 4.0 transformation. A specifically designed questionnaire is applied to SME’s with the support of KOSGEB (Small and Medium Sized Enterprises Development Organization), and in this stage of the research, the companies located in four major cities, namely Istanbul, Ankara, Izmir and Bursa, are analyzed and compared. The study aims to find out the level of awareness and readiness of SMEs in these cities and measure their Industry 4.0 scores. The final target is to support the Industry 4.0 implementations by defining the current situation and proposing suitable actions for adaptation based on varying results.
Keywords: Industry 4.0; Turkish Economy; Turkish Industry; Industry 4.0 Scorecard; Industrial Revolution; Endüstri 4.0; Türk Ekonomisi; Türk Endüstrisi; Endüstri 4.0 Puan Kartı